Vorticism and its allies. - Campbell, Robin; Cork, Richard; Lynton, Norbert; Arts Council of Great Britain, London (London : Hayward Gallery, 1974)
Arbuthnot, Malcolm ; Atkinson, Lawrence ; Bomberg, David ; Langdon Coburn, Alvin ; Dismorr, Jessica ; Epstein, Sir Jacob ; Etchells, Frederick ; Gaudier-Brzeska, Henri ; Hamilton, Cuthbert ; Nevinson, Christopher ; Roberts, William ; Saunders, Helen ; Shakespear, Dorothy ; Wadsworth, Edward ; Lewis, Wyndham ; Brodzky, Horace ; Bell, Vanessa ; Fry, Roger ; Grant, Duncan ; Turnbull, Jock ; Hamnett, Nina ; Bateman, H.M. ; Harrison, C. ; Sketch, The ; Sykes, Charles ; Sketch, Daily ; Titt', 'Tom ; Allinson, Adrian ; Marinetti, Filippo Tommaso ; Nevinson, Christopher ; Dyson, Will ; Kapp, Edmond X. ; Briscoe, E.E. ; Belenson, A. ; Quinn, John ; Allinson, Adrian ; Langdon Coburn, Alvin ; Roberts, William ; Meninsky, Bernard ; Dulac, Edmund
biografie
Engels
boek